TERJEBAK ELEKTORALISME: CATATAN TENTANG DEMOKRASI INDONESIA DUA DEKADE TERAKHIR - Natsir, Muh.; Ridha, Muhammad (JPP (Jurnal Politik Profetik), 2018)
This article collates on the argument that democracy built in Indonesia in the last two decades after the fall of the New Order regime has been increasingly electoral. It even forms of regime in electoral that extends its definition and practice to the lowest level of society such as at the district/city level or even at the village level. Unfortunately, this electoral progress has not been followed by social empowerment, justice and even distribution of economic resources. It even leads to an increasingly differentiated society that is materially more tangible or ownership of productive resources.